All ages welcome : recruiting and retaining younger generations for library boards, friends groups, and foundations - Bertinelli, Lina, 1988-; Jarvis, Madeline, 1990-; Kosinski, Kathy, 1990-; Wilson, Tess, 1990-; Association of Library Trustees, Advocates, Friends and Foundations (Chicago : ALA Neal-Schuman, 2020)
"With hands-on worksheets, brainstorming activities, checklists, and more, this planner provides practical tools for libraries to grow and strengthen their recruitment, retention, and training of trustees, Friends, and foundation members"--
Change Is Here and Will Be Here Again -- Generational Differences (and What We Have in Common) -- The ABCs of Recruitment and Retention -- Defining and Managing Diversity for Your Advocacy Group -- Onboarding: Tried and True Practices -- Fundraising with the Debt Generations -- Conclusion: Assess, Adapt, Attract.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
OCLC control number change
Keywords: Library trustees -- Recruiting -- United States; Friends of the library -- Recruiting -- United States; Volunteer workers in libraries -- Recruiting -- United States; Generation Y -- Employment -- United States; Library trustees -- United States -- Problems, exercises, etc; Friends of the library -- United States -- Problems, exercises, etc; Friends of the library; Library trustees; United States; Electronic books; Problems and exercises